STUDY ON THE ACCUMULATION OF COPPER FROM SOIL TO BIOMASS OF SOME VEGETABLES - Lê Thị Thanh Trân; Nguyễn Văn Hạ; Nguyễn Mộng Sinh; Nguyễn Ngọc Tuân (Tạp chí Khoa học Đại học Đà Lạt)
In this study, the accumulation of copper from soil to biomass of spinach, lettuce, carrot and potato was investigated. The results of this work showed that the absorption of copper from soil to these plants depended on biological features of each plant and thus, might be usefully applicable in agricultural cultivation of the mentioned plants.